Development of a Reverse Genetic System for Infectious Salmon Anemia Virus: Rescue of Recombinant Fluorescent Virus by Using Salmon Internal Transcribed Spacer Region 1 as a Novel Promoter - Spencer-Ossa, E; Mascayano-Collado, C; Cortez-San Martin, M; Toro-Ascuy, D (American Society for Microbiology, 2015)
Infectious salmon anemia (ISA) is a serious disease of marine-farmed Atlantic salmon (Salmo salar) caused by ISA virus (ISAV), belonging to the genus Isavirus, family Orthomyxoviridae. There is an urgent need to understand the virulence factors and pathogenic mechanisms of ISAV and to develop new vaccine approaches. Using a recombinant molecular biology approach, we report the development of a plasmid-based reverse genetic system for ISAV, which includes the use of a novel fish promoter, the Atlantic salmon internal transcribed spacer region 1 (ITS-1). Salmon cells cotransfected with pSS-URG-based vectors expressing the eight viral RNA segments and four cytomegalovirus (CMV)-based vectors that express the four proteins of the ISAV ribonucleoprotein complex allowed the generation of infectious recombinant ISAV (rISAV). We generated three recombinant viruses, wild-type rISAV901_09 and rISAVrS6-NotI-HPR containing a NotI restriction site and rISAVS6/EGFP-HPR harboring the open reading frame of enhanced green fluorescent protein (EGFP), both within the highly polymorphic region (HPR) of segment 6. All rescued viruses showed replication activity and cytopathic effect in Atlantic salmon kidney-infected cells. The fluorescent recombinant viruses also showed a characteristic cytopathic effect in salmon cells, and the viruses replicated to a titer of 6.5×105 PFU/ml, similar to that of the wild-type virus. This novel reverse genetics system offers a powerful tool to study the molecular biology of ISAV and to develop a new generation of ISAV vaccines to prevent and mitigate ISAV infection, which has had a profound effect on the salmon industry. © 2015, American Society for Microbiology.